Empagliflozin: the latest SGLT2 inhibitor on the block - Bhanwra, Sangeeta; Ahluwalia, Kaza (International Journal of Basic & Clinical Pharmacology, 2016)
Empagliflozin, the latest SGLT2 inhibitor is a selective, highly potent and competitive inhibitor of SGLT2 leading to the lowering of plasma glucose level by letting the sugar pass in the urine. It has a good safety and efficacy profile and is quite convenient to use for the patient as well, except for some increase in the urinary and genital mycotic infections in the recipients.